Osteochondral tissue engineering using a biphasic collagen/GAG scaffold containing rhFGF18 or BMP‐7 in an ovine model - Alan Getgood; Frances Henson; Carrie Skelton; Roger Brooks; Hans Guehring; Lisa A Fortier; Neil Rushton (Journal of Experimental Orthopaedics, 2014)
Abstract Background The aim of this study was to investigate the effect of combining rhFGF18 or BMP‐7 with a biphasic collagen/GAG osteochondral scaffold (Chondromimetic) on the repair of osteochondral defects in sheep. Methods Osteochondral defects (5.8×6mm) were created in the medial femoral condyle (MFC) and the lateral trochlea sulcus (LTS) of the stifle joint of 24 female sheep. Sheep were randomly assigned to four groups (n = 6); 1) empty defect, 2) scaffold only, 3) scaffold + rhFGF‐18 (30 μg) and 4) scaffold + BMP‐7 (100 μg). At 6 months the defects underwent non‐destructive mechanical testing, gross assessment of repair tissue (ICRS score) and histological analysis (Modified O’Driscoll score). Results ICRS repair score: Defects treated with scaffold + rhFGF18 (mean 9.83, 95% CI 8.43‐11.23) and scaffold + BMP‐7 (10, 9.06‐10.94) in the MFC had significantly improved ICRS scores compared to empty defects (4.2, 0–8.80) (p = 0.002). Mechanical properties: BMP‐7 treated defects (mean 64.35, 95% CI 56.88‐71.82) were significantly less stiff than both the rhFGF18 (mean 84.1, 95% CI 76.8‐91.4) and empty defects in the LTS, compared to both contralateral limb (p = 0.003), and the perilesional articular cartilage (p < 0.001). Histology: A statistically significant improvement in the modified O’Driscoll score was observed in the rhFGF18 treated group (mean 16.83, 95% CI 13.65‐20.61) compared to the empty defects (mean 9, 95% CI 4.88‐13.12) (p = 0.039) in the MFC. Excellent tissue fill, lateral integration and proteoglycan staining was observed. Only the rhFGF18 defects showed pericellular type VI collagen staining with positive type II collagen and reduced positive type I collagen staining. The majority of defects in the control and BMP‐7 groups demonstrated fibrocartilagenous repair tissue. Conclusion Statistically significant improvements in gross repair, mechanical properties and histological score were found over empty defects when Chondromimetic was combined with rhFGF18. These results suggest that rhFGF18 may play a significant role in articular cartilage repair applications.